2011
DOI: 10.1097/ypg.0b013e3283457a48
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic variation at the serotonin 1-A receptor gene is associated with comorbid depression and generalized anxiety

Abstract: In our study, the HTR1A C(-1019)G polymorphism was found to be associated to the frequent clinical presentation of comorbid MD and GAD, suggesting a common genetic background for mixed depression and anxiety states. These findings should be considered as preliminary. Future replications in independent samples would be needed to confirm or discard such association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 0 publications
0
28
0
5
Order By: Relevance
“…The impact of genetic variation in 5-HTR 1A in human experimental models may be investigated through a supposedly functional polymorphism in the 5-HTR 1A gene (rs6295, also referred to as C(-1019)G; see Albert, 2012). The G-allele of rs6295 has been associated with panic disorder (Rothe et al, 2004), comorbid generalized anxiety and major depression (Molina et al, 2011) and with panic symptoms (Huang et al, 2004;Choi et al, 2010). However, effects on mood and anxiety disorders were not demonstrated in another study (Hettema et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…The impact of genetic variation in 5-HTR 1A in human experimental models may be investigated through a supposedly functional polymorphism in the 5-HTR 1A gene (rs6295, also referred to as C(-1019)G; see Albert, 2012). The G-allele of rs6295 has been associated with panic disorder (Rothe et al, 2004), comorbid generalized anxiety and major depression (Molina et al, 2011) and with panic symptoms (Huang et al, 2004;Choi et al, 2010). However, effects on mood and anxiety disorders were not demonstrated in another study (Hettema et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…For example, in a study of a Caucasian Utah cohort with over 300 depressed and 300 control subjects, the G-allele was significantly enriched in depression by only 1.1-fold; the G/G genotype was 1.36-fold enriched [145]. Since these studies, several new association studies with the G-allele of rs6295 have been published for depression [101,146 -150], negative emotionality [151], anxiety [150,152], eating disorder [153], bipolar depression [104,147], alcohol withdrawal symptoms [154] and suicide [155]. One study suggests that the G-allele may be most strongly associated with depression with co-morbid anxiety [150], consistent with the importance of dysregulated Htr1a expression in both disorders.…”
Section: Association Studies Of Htr1a Polymorphisms In Depression-andmentioning
confidence: 99%
“…Most importantly, investigation of the association of rs6295 with a specific depression subtype (e.g. depression with co-morbid anxiety [150]) or specific endophenotypes (e.g. limbic activation, amygdala volume), appears to provide stronger associations in very small depression cohorts [124,157,173].…”
Section: Association Studies Of Htr1a Polymorphisms In Depression-andmentioning
confidence: 99%
“…22,23,25,26 Seven polymorphisms (BCL2, DRD2, HTR1A, BDNF, MAOA, 5HTT, TPH) had their genotypic and allelic frequencies reported. Among these, the following association with Generalized Anxiety Disorder were described: (a) the Met allele of the BDNF gene was associated with increased BDNF protein levels in GAD; 22 (b) the 941T allele of the MAOA gene was associated with GAD in females; 23 (c) the SS genotype and S allele of the 5-HTT gene were associated with GAD; 26 (d) the A allele of the ERS2 gene was associated with an increased risk of GAD, but the authors failed to report the frequency of allele occurrence. Moreover, the size of the samples of cases and and controls in the published studies varies greatly, which reduces the reliability of the results.…”
Section: ■ Resultsmentioning
confidence: 99%
“…28 A crude association between the C (-1019)G polymorphism of HTR1A and GAD has been reported (p = 0.003). 28 Molina et al 22 reported a main effect of the G(-1019) allele of the HTR1A gene on comorbid MD-GAD (p = 0.005).…”
mentioning
confidence: 99%